Prevalence of SARS-CoV-2 infection in the workplace: results of a year of investigation in the Marche Nord companies - Orlandi, Chiara; Orlandi, Chiara; Schiavano, Giuditta Fiorella; Brandi, Giorgio; Magnani, Mauro; Casabianca, Anna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The world of work has been profoundly affected by the COVID-19 pandemic since workplace activities involving close contact with coworkers and customers can lead to transmission of SARS-CoV-2 and compromise continuity of operations of workplaces.The Covid-Lab of University of Urbino and the Confindustria Pesaro Urbino association signed an agreement to support the Marche Nord companies in the adoption of anti-contagion safety protocols.Methods: Antibodies detection was performed using a rapid immunochromatographic test. Total RNA from nasopharyngeal swab was subjected to a real-time RT-PCR multiplex for the detection of RdRp specific gene and E gene of the SARS-CoV-2, and the internal control (human RNase P).Results: Between May 2020 and Apr 2021, over 10,000 rapid serological tests had been carried out on workers of 35 companies and in 5% of cases IgG or IgM were found (519). All the 519 swabs gave a valid result (RNAse P Ct≤40) with 105 positive results (20%) for SARS-CoV-2 with a Ct value ≤45. Overall, only 1% of samples resulted positive for viral RNA (105/10000).Conclusions: The University of Urbino set up a rapid-response (within 24 h, generally